Implementasi Metodologi Agile dalam Pengembangan Platform Kursus Online pada Platform Eduskill - Muhammad Hariz Izzuddin; Muhammad Daniel Krisna Halim Putra (Journal on Education, 2024)
The gap between industry needs and workforce skills in information technology necessitates more adaptive educational solutions. This research aims to implement Agile methodology in the development of the Eduskill online course platform, focusing on video course online and mentorbot features. The research methods used include observation, interviews, and literature review. The results show that the application of Agile Scrum allows the team to work iteratively and responsively, improving product quality and speeding up delivery times. The video course online feature provides an interactive learning experience, while the mentorbot offers AI-based personalized learning support. Agile implementation ensures that both features are continuously updated and relevant to user needs.